Chronic undernutrition amongst under-five in an urban slum of Central India - Dhok, Rajeshree S.; Thakre, Subhash B. (International Journal Of Community Medicine And Public Health, 2017)
Background: Malnutrition is a major public health problem in India. Chronic undernutrition - stunting is one of the major causes of morbidity and mortality among under-five children. It continues to be a growing problem in most developing countries. Present study was planned to estimate prevalence of stunting (chronic undernutrition) and its determinants amongst under-five children in an urban slum of central India. Methods:This community based cross-sectional study was conducted in an urban slum area of Nagpur, India. Study subjects were under five children residing in the slum. Data collection was done by conducting house to house survey and information was recorded in pre-designed pre-tested survey tool. Height was measured with standard techniques and classified as stunting according to WHO child growth standards 2006. Results: The overall prevalence of stunting amongst under five children in urban slum area was found to be 34.77%. Determinants found to be significantly (P<0.05) associated with stunting were lower socio-economic status, illiteracy of mother, working status of mother, separated marital status of mother, not exclusively breastfed for 6 months, duration of breastfeeding <2 years, immunization not appropriate for age. Conclusions:Stunting still continues to exists as problem among under five children of urban slum. Efforts need to be directed towards maternal education, promotion of optimal infant & young child feeding practices and immunisation as these factors are significantly associated with stunting.